Peripheral blood stem cell collection for allogeneic hematopoietic stem cell transplantation: Practical implications after 200 consequent transplants. Issue 6 (December 2017) - Goren Sahin, Deniz; Arat, Mutlu
Abstract: Background: Proper stem cell mobilization is one of the most important steps in hematopoietic stem cell transplantation (HSCT). The aim of this paper is to share our 6 years' experience and provide practical clinical approaches particularly for stem cell mobilization and collection within the series of more than 200 successive allogeneic HSCT at our transplant center. Subjects & Methods: Two hundred and seven consecutive patients who underwent allogeneic peripheral blood stem cell transplantation were included in this study. Age, sex, weight, complete blood counts, CD34 + cell counts, total collected amount of CD34 + cells, CD34 + cells per 10 l processed, mobilization failure and adverse events were reviewed. Results: Median age was 40.2 ± 12.9 (21–68) years and 46.4 ± 13.4 (17–67) years for donors and patients, respectively. The number of donors who had undergone adequate CD34 + cell harvesting and completed the procedure on the fourth day was 67 (32.8% of all patients). Only 12 patients required cell apheresis both on day 5 and 6. Apheresis was completed on day 4 and/or day 5 in 94.2% of all our donors. There was no significant association between CD34 + stem cell volume and age, gender and weight values of donors. Mobilization failure was not seen in our series. Conclusions: G-CSF is highly effective in 1/3 of the donors on the 4th day in order to collect enough number of stem cells. We propose that peripheral stem cell collection might start on day 4th of G-CSF treatment for avoiding G-CSF related side effects and complications.